Legal liability for environmental damage compensation by mining companies in Raja Ampat - Suhardin, Yohanes; Siahaan, Rudy Haposan; Zendrato, Selatieli (Frontiers in Sustainability, 2026)
Mining companies in Raja Ampat have sparked pressure from Commission IV of the Indonesian House of Representatives (DPR RI) to demand that four mining companies, whose business licenses have been revoked, pay for the damage caused by mining activities that violate environmental regulations in implementing Presidential Regulation Number 5 of 2025 on Forest Area Regulation by adhering to the principles of sustainability and environmental protection. The method used in this research focuses on the application of law in society, its impact, and the interaction between law and social behavior by using a case study approach to analyze legal issues through specific case studies. The results of this study indicate issues with supervision in the permit issuance process and company productivity, leading to violations that cause extensive environmental damage. The law enforcement of the sanctions imposed on the Company is not strict and does not meet the principle of administrative sanctions as a means of public law, which involves the imposition of burdens by the government on its citizens in response to non-compliance with obligations arising from legislation, also known as in cauda venenum, the poison in the tail.